Valorization of Food Industries Wastes for the Production of Poly(vinyl) Alcohol (PVA) Biodegradable Composites - Ferrari, Francesca; Striani, Raffaella; Esposito Corcione, Carola; Greco, Antonio (Frontiers in Materials, 2019)
This work is aimed to the development of new green composite materials by the incorporation of natural additives into poly(vinyl) alcohol (PVA). Two additives, shredded walnut shells and organic fraction of municipal solid waste (MW), were used to improve the mechanical properties of PVA. Both additives, derived from food industry wastes, were added in a PVA/water solution, which allowed to produce samples by the use of a pressure free process. Rheological analysis was performed in order to study the evolution of the material viscosity during thermal treatment, aimed at water removal. Samples obtained were characterized by means of differential scanning calorimetry (DSC), showing an improvement of the glass transition temperature brought by the addition of walnut shells. Finally, flexural tests were carried out on samples obtained after the incorporation of the different additives in PVA and compared with the mechanical properties of the neat matrix. Results obtained indicate the potential improvement brought by the addition of walnut shells, which allows increasing the flexural modulus of about 50%, at the expenses of a flexural strength reduction of about 30%. Also, at least for low amount of added water, the addition of MW was shown to provide an increase of the strain at break equal to 100%.